2007
DOI: 10.1080/01496390701289948
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Nitrobenzene from Water onto High Silica Zeolites and Regeneration by Ozone

Abstract: This work investigates the removal of nitrobenzene (NB), a model pollutant from water, by combining adsorption onto zeolites and regeneration with ozone. The adsorption equilibrium isotherms of NB onto zeolites enabled the best adsorbent to be selected and zeolites with a high Si/Al ratio were the most efficient. The adsorption capacity depended on the Si/Al ratio and on the pore size. In a sequential process coupling adsorption and oxidation by ozone, NB was completely removed from water and the initial adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 10 publications
(23 reference statements)
2
29
1
1
Order By: Relevance
“…posses a high Si/Al ratio [15,17,20,21]. Therefore, the adsorptive properties of various zeolites towards the adsorption of phenol from aqueous solutions have to be investigated and verified by adequate experimental methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…posses a high Si/Al ratio [15,17,20,21]. Therefore, the adsorptive properties of various zeolites towards the adsorption of phenol from aqueous solutions have to be investigated and verified by adequate experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…An important property of these materials is the capacity to be regenerated while keeping their initial properties. Synthetic and natural zeolites have been widely used as adsorbents, catalysts, ion exchangers, membranes and molecular sieves; however, the application of synthetic zeolites for removal of phenolic compounds from wastewaters is covered in a limited extent in literature [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The R L value of Cu/AC was found to be 0.084, indicating that the adsorption of NB on Cu/AC is favorable. Whereas for activated carbon the Freundlich isotherm is the suitable model to describe the experimental data, Renguoat et al also found that the Freundlich model fitted well the adsorption isotherm of NB on activated carbon compared to silica [42].…”
Section: Adsorption Isothermsmentioning
confidence: 94%
“…This is the case with nitrobenzene [140], a highly refractory pollutant. Furthermore, it has been observed that some adsorbents with high-Si/Al ratio could degenerate the ozone molecule to its radical specie such that it is able to effectively degrade organic pollutants even refractory organics like nitrobenzene with improved adsorption capacities of the adsorbents and higher selectivity for polar compounds [141,142]. This was attributed to a surface modification of the adsorbent, by highly reactive species generated during molecular ozone decomposition in the course of regeneration.…”
Section: Ozonationmentioning
confidence: 96%